Bacteriology and antibiotic sensitivity in gynaecological abdominal surgical site infections - Panda, Sandhyasri; Lepakshi, Sarepalli Sai Sindhura Puja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Surgical site infection increases the rate of re hospitalisation, the use of health care, diagnostic, and therapeutic resources, and hospital costs. Severe sequelae may exacerbate primary and devastating infections. About 39-51% of pathogens causing surgical site infections were documented to be resistant to standard prophylactic antibiotics. This study aimed to calculate surgical site infection rate at our hospital. To identify the isolates causing surgical site infections and study anti-microbial susceptibility pattern of isolated organisms. Methods: This observational study was done among patients who underwent abdominal gynaecological surgeries and who developed surgical site infection in department of obstetrics and gynaecology in Maharajahs institute of medical sciences during May 2022 to April 2024. Results: Surgical site infection rate at our hospital is 18.29%, there are 30 surgical site infections, 76.7% cases are culture positive, 23.3% cases are sterile, 52.2% cases are gram negative, 47.8% are gram positive. Most common organism isolated is E. coli (39%) followed by Staphylococcus aureus (26%), enterococcus (21.7%), Pseudomonas (8.6%), Klebsiella (4.3%). Antibiotic susceptibility pattern shows maximum overall sensitivity of organisms to amikacin (65.4%) followed by gentamicin (56%), piperacillin tazobactum (52.17%), amoxyclav (47.8%) followed by rest of drugs. Conclusions: Practice of routine culture and sensitivity of surgical site infections can prevent grave complications, limit cost of treatment, prevent fast emerging antimicrobial resistance. In our study, complications are limited to need for secondary suturing. The most susceptible drug in our study is amikacin, thus, it can be incorporated as a part of empirical treatment in patients with surgical site infection before the culture sensitivity report is obtained.